The process of establishment of the Ashtarkhanid state - Moydinov Muhammadali (Zien Journals, 2023)
In this article , detailed information is given about the issues related to the rise of the Ashtarkhanid dynasty and the transition of the country to the stage of political development . In addition, in this article, the list of the rulers of the Ashtarkhanid dynasty is presented chronologically
Keywords: Ashtarkhanids; Asrtrakhan; Abdullah